2015
DOI: 10.1152/japplphysiol.00147.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of swimming exercise on three-dimensional trabecular bone microarchitecture in ovariectomized rats

Abstract: Swimming is generally considered ineffective for increasing bone mass in humans, at least compared with weight-bearing sports. However, swimming exercise has sometimes been shown to have a strong positive effect on bone mass in small animals. This study investigated the effects of swimming on bone mass, strength, and microarchitecture in ovariectomized (OVX) rats. OVX or sham operations were performed on 18-wk-old female Fisher 344 rats. Rats were randomly divided into four groups: sham sedentary (Sham-CON), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…They were then subjected to swimming exercise (45–60 min/day, 5 times/week) for 8 weeks. The temperature of the water was maintained at 36°C ± 2°C, at which the core temperature is not affected 14 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were then subjected to swimming exercise (45–60 min/day, 5 times/week) for 8 weeks. The temperature of the water was maintained at 36°C ± 2°C, at which the core temperature is not affected 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Ju et al . reported increased femoral density and trabecular size after 12 weeks of swimming exercise, and found that muscle contraction during swimming exercise can sufficiently improve bone mineral density 14 . However, with numerous suggestions that underwater exercises such as swimming, in which the load is reduced by buoyant force, hinder improvement in bone mineral density 1 , 24 , further investigation is necessary to clarify the effects.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…(19,20) Non-weightbearing-swimming exercise also prevented bone loss associated with ovariectomy or hindlimb suspension. (21)(22)(23) In the following study, we investigated the effect of weight-bearing (voluntary wheel-running) and non-weight-bearing-(swimming) physical activity on musculoskeletal mass and strength in wild type (WT) and homozygous OI murine (oim/oim) mice. Gentry and colleagues were the first to identify an intrinsic muscle pathology in OI by demonstrating that oim/oim mice have reduced specific muscle contractile function (described as the peak tetanic force normalized to myofiber cross sectional area) as compared with WT littermates.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, physical exercise can act as an important non-drug intervention, increasing BMD and bone tissue resistance. Exercises with no impact, such as swimming and cycling, do not demonstrate an effect on improving BMD 12,13 ; however, studies that used swimming to reverse a BMD reduction framework caused by the absence of mechanical stimuli showed effectiveness in increasing BMD after swimming exercise 2,12,14 . In the present study, although there was no difference between the ET4 and BL groups, the animals that performed the aerobic swimming exercise demonstrated increased BMD after eight weeks of training (ET8), compared to the BL group without intervention.…”
Section: Discussionmentioning
confidence: 99%